UPAYA PEMERINTAH DALAM PENYELESAIAN KONFLIK ANTAR OKP - Arina Risqi; Dhiauddin Tanjung (Law Development Journal, 2023)
The purpose of this study is to find out how the public views the existence of Youth Community Organizations in the city of Medan and what is the role of the Medan City government in efforts to resolve conflicts between Youth Community Organizations in Medan City. The research method used was field research using qualitative methods, with a case study approach and data collection techniques using participant observation and direct interviews with the people of Medan City. Efforts to resolve the conflict that has been carried out so far is mediation accompanied by the police. From the Medan City Government, because conflicts often occur in Medan Belawan, forming a Conflict Resolution Team to resolve conflict issues. The community thinks that the city government's settlement efforts are not quite right, it's not surprising that the community prefers to disband youth organizations that cause a lot of trouble. However, a few of the people felt there was benefit from the existence of the Youth Community Organization in Medan City.